Application of Cognitive Restructuring Technique to Reduce Fear of Missing Out in Social Media Use Among Vocational High School Students - Rafli Adriansyah Rahman; Farida Aryani; Aswar Aswar; Sinta Nurul Oktaviani Kasim (International Journal of Research in Counseling, 2026)
High social media use among adolescents contributes to Fear of Missing Out (FoMO), an anxiety driven by cognitive distortions that encourages compulsive online engagement. Vocational high school students are particularly vulnerable because demanding academic and practical training schedules often lead them to seek psychological compensation through social media. This study aimed to: (1) describe students’ FoMO levels before and after the intervention, (2) explain the implementation of cognitive restructuring in group counseling, and (3) examine its effectiveness in reducing FoMO. A quantitative quasi-experimental design with a non-equivalent control group was employed. Twenty eleventh-grade students with high FoMO scores were assigned to an experimental group (n = 10) and a control group (n = 10). Data were collected using an adapted FoMO Scale (28 valid items; Cronbach’s Alpha = 0.907). The intervention consisted of seven group counseling sessions based on Cormier and Cormier’s (1985) six-stage cognitive restructuring model. The independent samples t-test showed a significant effect (t = 16.906, p < .001). Students in the experimental group improved from high/very high to moderate/low FoMO levels, whereas the control group showed no meaningful change. These findings provide empirical evidence that structured cognitive restructuring is effective for reducing FoMO among vocational high school students and supports its integration into school guidance and counseling services to promote adolescents’ digital wellbeing.